2014
DOI: 10.1111/bij.12218
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation and speciation in the genusCharacidium(Characiformes: Crenuchidae): effects of reproductive and chromosomal barriers

Abstract: Both time and low gene flow are the key factors by which different biological species arise. The divergence process among lineages and the development of pre-or postzygotic isolation occur when gene flow events are lacking. The separation among species of the genus Characidium was analysed in relation to the geomorphological mechanisms in river courses, events of captured adjacent upland drainages in south-eastern Brazil, and sex chromosome differences. The ZZ/ZW sex chromosomes of Characidium vary in size, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 36 publications
5
43
0
Order By: Relevance
“…paleatus, and C. lacrimostigmata shows some variation in the localization of heterochromatin. These are likely due to population-specific repetitive DNA accumulation in the absence of gene flow, a process previously suggested for other fish taxa (e.g., Vicari et al, 2010;Pucci et al, 2014). FISH analyses revealed a differentiated pattern of both location and number of 18S and 5S rDNA sites among the populations studied here.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…paleatus, and C. lacrimostigmata shows some variation in the localization of heterochromatin. These are likely due to population-specific repetitive DNA accumulation in the absence of gene flow, a process previously suggested for other fish taxa (e.g., Vicari et al, 2010;Pucci et al, 2014). FISH analyses revealed a differentiated pattern of both location and number of 18S and 5S rDNA sites among the populations studied here.…”
Section: Discussionsupporting
confidence: 69%
“…We also utilize Fluorescence in situ hybridization (FISH), which permits the mapping of molecular markers by localizing DNA probes with a specific sequence within a target sequence (Pinkel et al, 1986). FISH techniques are a powerful tool for the localization of chromosomal rearrangements, especially with site-specific probes that can identify rearranged regions when it is difficult to detect banding patterns in a karyotype (Pucci et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This group is an excellent model for studies of sex chromosome differentiation because some species present a highly differentiated ZZ/ZW sex system, while others do not have any heteromorphic sex chromosomes. At present, Characidium sex chromosomes are thought to have a single origin, and the proto-sex chromosome was likely NOR bearing [Vicari et al, 2008;Machado et al, 2011;Pansonato-Alves et al, 2014;Pucci et al, 2014]. Subsequently, distinct events such as an increase/decrease in size, NOR translocation and heterochromatinization have shaped sex chromosome diversification in each Characidium species/population [Vicari et al, 2008;Pansonato-Alves et al, 2010, 2011aMachado et al, 2011;Pucci et al, 2014].…”
Section: Chromosomal Mapping Of Repetitive Dnas Inmentioning
confidence: 99%
“…However, reassociation kinetics based on C o t-1 DNA and the microdissection of chromosomes submitted to C-banding and the subsequent amplification of heterochromatic sequences using degenerate oligonucleotide-primed polymerase chain reaction (PCR) have been used successfully. [9][10][11][12][13][14] The Parodontidae is a Neotropical fish group that is divided into three genera: Parodon, Apareiodon, and Saccodon. 15 Cytogenetic studies reported a conserved diploid number of 54 chromosomes in Parodontidae with distinctive karyotype formulae and numerical/position variation of 18S and 5S rDNA sites.…”
mentioning
confidence: 99%